Enhanced Impingement Jet Cooling of Gas Turbine Wall Heat Transfer using CFD CHT Code: Influence of Wall Thermal Gradient with Fin and Dimple Obst - El-Jummah, A. M.; Andrews, G. E.; Staggs, J. E. J. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
Gas turbine (GT) jet cooling using the regenerative or impingement jet backside cooling system is applicable to low NOx GT combustors and was investigated in the present work. The impingement heat transfer investigated is for the techniques where all the combustion air is used for wall cooling prior to passing through the flame stabiliser. Ten rows of impingement holes were modelled and are for four different types of obstacles: rectangular-pin in co- and cross-flows, circular pin-fin in cross-flow and dimple in direct-flow configurations, arranged in the impingement jet air flow direction. Conjugate heat transfer (CHT) and computational fluid dynamics (CFD) techniques were combined and applied in the computational analysis. Only the two obstacles in rectangular shape: co- and cross-flow configurations were validated against experimental results, as the other two has no experimental data available, but similar CFD methodology was applied. The impingement jet cooling enhancing obstacles were aligned transverse to the direction of the impingement jet cross-flow on the target surface and were equally spaced on the centre-line between each row of jet holes transverse to the cross-flow. Also, one heat transfer obstacle was used per impingement jet air flow in order to see the level of heat transfer augmentation of each one.  The CFD calculations were carried out for an air mass flux G of 1.08, 1.48 and 1.94 kg/sm2bar, hence for each obstacle grid geometry, three computations were conducted and therefore a total of twelve different computations for this investigation. These high mass flux used, are only applicable to the regenerative combustor wall cooling applications. Validation of the CFD predictions with the experimental data indicates good agreement for impingement gap flow pressure loss (ΔP/P) and the surface average heat transfer coefficient (HTC), h. Other predictions were also carried out and were for locally average X2 HTC, hole exit pressure loss, turbulence kinetic energy (TKE), flow-maldistribution, Nusselt number (Nu) and normalized temperature, T* or thermal gradient. It was concluded here that the rectangular-pin obstacles have the highest exit hole and impingement gap pressure loss, but with low heat transfer as a result of higher flow-maldistribution. Dimple obstacle has the lowest heat transfer, but is because most of the heat is taken away (or sucked in) by the dimple pot. The main effect of the obstacles was to increase the heat transfer to the impingement jet surface, but the dimple surface was predicted to have a very poor performance, with significantly reduced target wall heat transfer and thermal gradient.